Strengthening multi-sectoral participation in watershed management the case of the Wawa watershed in Sitio Wawa, Barangay San Rafael, Rodriguez, Rizal - Plaza, Aldrin B (2007)
This study looks into how multi-sectoral participation can effectively play a role in the formulation of management strategies and on on-site administration of the Wawa Watershed.